Interplay between cracking and delamination in incrementally deposited plasma sprayed coatings - Shinde, Shalaka V.; Sampath, Sanjay (Acta materialia, 2021)
Cracking and delamination in constrained films and coatings during fabrication and service has been an important subject of scientific inquiry for several decades. Considerable past efforts have focused on developing analytical models based predicting steady state energy release rates to determine the occurrence of either cracking and/or delamination in thin films. Such models have been reconciled into a ‘Design Map’. However, the extent of available experimental validation of such Design Maps is limited. In addition, these analytical Design Maps lack the description of nuances in the processing of layered films such as progressive incremental deposition. In this study, the interplay between cracking and delamination in progressively deposited plasma sprayed coatings is defined based on the aforementioned models. Following the adaptation of the models and presiding assumptions, a carefully designed set of experiments to probe responses from different ceramics and process conditions have been conducted, which allowed the controlled observation of cracking and/or delamination events. These experiments elucidated the underlying conditions that determine the onset of such stress relaxation events. The experimental data is reconciled with an adapted analytical Design Map for single, isolated, rapidly solidified droplets (splats) and for incrementally deposited thick plasma sprayed coatings, thus providing a framework for the robust design and processing of advanced coatings. [Display omitted]